Dental Fluorosis and Catalase Immunoreactivity of the Brain Tissues in Rats Exposed to High Fluoride Pre- and Postnatally - MENTEŞ, ALİ RECAİ; HAZNEDAROĞLU, EDA; BOZKURT, SÜHEYLA (HUMANA PRESS INC, 2016)
This study evaluated dental fluorosis of the incisors and immunoreactivity in the brain tissues of rats given chronic fluoride doses pre- and postnatally. Female rats were given drinking water with 0, 30 or 100 ppm fluoride ad libitum throughout gestation and the nursing period. In addition, 63 male offspring were treated with the same water regimens as the mothers after weaning and were followed for 1, 3 or 5 months. The upper and lower incisors were collected, and all teeth were examined under a stereomicroscope and scored by two blinded examiners using a modified rodent enamel fluorosis index. Cortical, hippocampal and cerebellar brain samples were evaluated morphologically and immunohistochemically. All fluoride-treated pups were born with low body weight (p = 0.001). All animals from the fluoride groups had enamel fluorosis with defects of various degrees. The increase in the dental fluorosis scores in the fluoride treatment groups was significant (p < 0.01). The catalase immunoreactivity in the 30- and 100-ppm fluoride groups was significantly higher than that in the controls after 1, 3 and 5 months (p < 0.001). In conclusion, this study showed that rats with dental fluorosis had catalase immunoreactivity in the brain tissues, which may reflect the neurobehavioral toxicity of fluoride.
Keywords: Fluoride toxicity; Dental fluorosis; Brain; Catalase; Rats; CENTRAL-NERVOUS-SYSTEM; OXIDATIVE STRESS; SODIUM-FLUORIDE; INFANT FORMULA; APOPTOSIS; MICE; NEUROTOXICITY; AMELIORATION; ASSOCIATION; CALCIUM